2023
DOI: 10.1212/wnl.0000000000207070
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and Depression

Abstract: When 2 medical conditions occur together more often than predicted by chance, they are called comorbid conditions. The observation that depression is connected to epilepsy (i.e., that they are comorbidities) raises many questions. How are the illnesses connected? Are both caused by a common underlying brain abnormality? Is there an abnormality of neurotransmitters responsible for both? Finally, does the same connection occur with other chronic medical illnesses? The authors of this study used asthma, another c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Previous studies revealed that in patients with epilepsy, a nearly 2-fold increase in the risk of developing depression was observed[ 31 ]. Furthermore, if people are first diagnosed with depression, the risk of developing epilepsy increases 2.5-fold[ 33 ]. In addition, another study demonstrated that epilepsy is not only associated with an increased risk of depression but also with the severity of epilepsy[ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that in patients with epilepsy, a nearly 2-fold increase in the risk of developing depression was observed[ 31 ]. Furthermore, if people are first diagnosed with depression, the risk of developing epilepsy increases 2.5-fold[ 33 ]. In addition, another study demonstrated that epilepsy is not only associated with an increased risk of depression but also with the severity of epilepsy[ 34 ].…”
Section: Discussionmentioning
confidence: 99%